2019
DOI: 10.1108/apjie-10-2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

Does innovation capabilities affect the new service innovation success among Pakistani cellular companies?

Abstract: Purpose In today’s Pakistan, the emergence of new forms of business in collaboration with the mobile service providers is bringing a big difference, not only in every walk of life but also in digital economy of the country. Therefore, the purpose of this paper is to explore what are the factors that determine the success rate of new innovative services in cultural context of mobile service providers of Pakistan. Design/methodology/approach Data have been collected from 397 employees of cellular firms of Paki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
13
0
1
Order By: Relevance
“…Customer orientation and innovativeness A study by Kiani et al (2019) revealed that enhancing the capabilities of organization to innovate in terms of better understandings of customer needs and the available technological options of the competitive market dynamics would be helpful for the practitioners to attain the overall success of services in short-and long-term perspectives. Previous studies indicated that a concentration on customer orientation results in various performance outcomes.…”
Section: Literature Review and Hypothesis Development Market Orientatmentioning
confidence: 99%
“…Customer orientation and innovativeness A study by Kiani et al (2019) revealed that enhancing the capabilities of organization to innovate in terms of better understandings of customer needs and the available technological options of the competitive market dynamics would be helpful for the practitioners to attain the overall success of services in short-and long-term perspectives. Previous studies indicated that a concentration on customer orientation results in various performance outcomes.…”
Section: Literature Review and Hypothesis Development Market Orientatmentioning
confidence: 99%
“…However, it is also indicated by literature that there is a need to study the innovation capabilities and the concept of business model innovation in lieu of some performance indicators that could be success of service innovation. It is essential to explain here that the stronger the innovation capabilities may yield more success in newly offered services, consequently this would enable the organization to carry the innovation in its business model by breaking its static nature (Kiani, Mustafa, & Ahmad, 2019). The dynamic and changing market needs of the industry requires the organization to break the static shells of their traditional business model in order to offer more customized and value service delivery, in addition, to capture and proposition of value for itself.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…It has also been found from the review of literature that the different researchers have conducted detailed research on the concept of innovation capabilities in varying perspectives (Kiani, Mustafa, & Ahmad, 2019;Kiani, Ahmad, & Gillani, 2019). Despite the existence of researches relating innovation capabilities, still there is a need to further validate this construct.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kungu, Desta and Ngui [38], innovation is the practice whereby new thoughts and concepts are converted into sustainable value-creating outcomes. Recently, [39] maintain that innovation has three main dimensions, such as: new service ideas, new service processes, and new technological systems that proved to be useful in describing the diversity of service innovations. These dimensions can be employed as performance indicators regarding service innovations, and also suitable as performance measurement variables.…”
Section: Introductionmentioning
confidence: 99%
“…These dimensions can be employed as performance indicators regarding service innovations, and also suitable as performance measurement variables. Bearing this in mind, there is still a need to better understand the role of innovation as an important antecedent construct of service success [39,40].…”
Section: Introductionmentioning
confidence: 99%